Antimicrobial Activity of Spanish Propolis against Listeria monocytogenes and Other Listeria Strains - Eugenia Rendueles; Elba Mauriz; Javier Sanz-Gómez; Félix Adanero-Jorge; Camino García-Fernandez (Microorganisms, 2023)
The outbreaks of Listeria associated with food consumption are increasing worldwide concurrently with public concern about the need for natural growth inhibitors. In this context, propolis seems to be a promising bioactive product collected by honeybees, due to its antimicrobial activity against different food pathogens. This study aims to evaluate the efficacy of hydroalcoholic propolis extracts for controlling Listeria under several pH conditions. The physicochemical properties (wax, resins, ashes, impurities), the bioactive compounds (phenolic and flavonoid content), and the antimicrobial activity of 31 propolis samples collected from the half North of Spain were determined. Results showed similar trends in the physicochemical composition and bioactive properties, regardless of the harvesting area. Non-limiting pH conditions (7.04, 6.01, 5.01) in 11 Listeria strains (5 from collection and 6 wild strains from meat products) exhibited MICs (Minimum inhibition concentration) and MBCs (Minimum bactericidal concentration) ranging from 39.09 to 625 μg/mL. The antibacterial activity increased under acidic pH conditions, showing a synergistic effect at pH = 5.01 (p < 0.05). These findings suggest the potential of Spanish propolis as a natural antibacterial inhibitor to control Listeria growth in food products.